Tracing the Roots of Socio-Cultural Factors in Legal and Religious Thought: Historical and Contemporary Perspectives - M Mahmudulhassan; Sazirul Begum; Saif Uddin Ahmed Khondoker; Alberto Emmanuel Conti Morales; M Muthoifin; Wildan Mahir Muttaqin (Walidem Institute and Publishing, 2024)
This study aims to identify and analyze the socio-cultural factors that form the background of Islamic legal thinking, both in historical and contemporary contexts. Thus, this study seeks to understand how socio-cultural factors influence the development and interpretation of Islamic law over time. This research uses a qualitative approach by conducting a literature review as well as a historical and contemporary analysis of the development of Islamic law. Data is obtained through literature studies that include primary and secondary sources, such as classical Islamic law books, historical texts, and related academic studies. The results showed that socio-cultural factors have a significant role in shaping Islamic legal thinking. From a historical perspective, the development of Islamic law is often influenced by the socio-cultural context in which it developed, such as customs, customs of society, and political-economic conditions. Meanwhile, in the contemporary perspective, globalization, modernization, and other socio-cultural changes also affect the interpretation and application of Islamic law in society. This study concludes that understanding socio-cultural factors is very important in understanding the dynamics of Islamic legal thought. By considering the socio-cultural context, Islamic legal thinkers can develop relevant and adaptive approaches in formulating legal solutions that are by the demands of the times.